Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1177/0170840600213004
|View full text |Cite
|
Sign up to set email alerts
|

Haute Couture and Prêt-à-Porter: The Popular Press and the Diffusion of Management Practices

Abstract: The transformation of management practices has recently become the object of many theoretical and empirical works. While most of these works focus mainly on universities, business schools and consulting firms, our paper aims at investigating the still largely unexplored role of the popular press in the production and legitimation of management ideas and practices. Based on the content analysis of the articles on human resource management published in the last decade in leading newspapers and magazines in Italy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(56 citation statements)
references
References 23 publications
2
48
0
4
Order By: Relevance
“…As regards supply side actors, important channels for presenting ideas to potential adopters were conferences, books and professional journals (Mazza, 1998;Mazza and Alvarez, 2000;Thomas, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards supply side actors, important channels for presenting ideas to potential adopters were conferences, books and professional journals (Mazza, 1998;Mazza and Alvarez, 2000;Thomas, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…supply side factors. Alvarez (1998) and Mazza and Alvarez (2000) stress the importance of making innovations compatible with the societies to which they are transmitted (diffused). They also argue that cultural discourses and legitimisation are the main resources needed to enable the popularisation of an innovation.…”
mentioning
confidence: 99%
“…In fact, this tendency to concentrate on analyzing discourses without thoroughly assessing material consequences in terms of adoption behavior is not confined to research on the diffusion of CSR practices, but has been described as a limiting factor of much diffusion research from an institutional theory perspective within the past years (Zilber 2008;Mazza and Alvarez 2000). In order to contribute to closing these gaps, I will combine existing theoretical arguments from institutional theory in order to derive empirically testable propositions on how reporting by infomediaries on codes of conduct within an industry should interrelate with organization's adoption behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, it has been argued that infomediaries might influence diffusion through the way they interpret Dressing up for Diffusion and frame organizational practices-irrespective of reporting intensity (Hirsch 1986;Strang 1997;Mazza and Alvarez 2000). Existing research has thereby identified two central aspects of meaning construction that might affect adoption decisions by consumers of discourses produced by infomediaries surrounding the diffusion of an organizational practice: (1) explanatory accounts and (2) frames of reference.…”
Section: Infomediaries and Materials Practice Diffusionmentioning
confidence: 99%
See 1 more Smart Citation